Economic Valuation of Community Losses from Water and Air Quality Degradation in Nickel Mining Activities - La Maga; Dominggus Marei (AIBPM Publisher, 2026)
Unsustainable use of natural resources can cause environmental damage. As in the nickel mining activities of PT. X, water, and air pollution cause diseases such as itchy skin and coughs. The purpose of this study is to analyze the economic impacts of water and air pollution. The study was conducted in the Tinanggea District, covering Lapoa and Bomba-Bomba Villages. The research location was determined using purposive sampling because residents in both villages experienced negative impacts from pollution. This study used a quantitative descriptive approach with economic valuation. Quantitative data were obtained through interviews with 45 rice farmers. Community losses were estimated using the cost-of-illness method, lost income, and decreased productivity. The value of losses due to water quality degradation includes medical costs of IDR 15,974,604/Year and lost income costs of IDR 55,650,604/Year. Air pollution causes coughs suffered by children in Lapoa and Bomba-Bomba Villages. This analysis uses only the medical cost approach, which is IDR 1,089,000/Year. The total loss due to water and air pollution is estimated at IDR 72,714,208/Year. Therefore, government supervision of nickel mining activities is needed, while PT. X must restore environmental quality to prevent further harm to the community